Penetapan Ambang Batas Calon Presiden dan Wakil Presiden Berdasarkan UU No. 23 Tahun 2003 dan UU No. 7 Tahun 2017 - luken ferisman lubis; Eddy Asnawi; Bagio Kadaryanto (DOKTRINA: JOURNAL OF LAW, 2023)
The purpose of this study is how the threshold for the nomination of president and vice president is based UU No. 23 Year 2003 and UU No. 7 Year 2017 and how ideally the threshold for presidential and vice presidential candidates is determined based on UU No. 23 Year 2003 and UU No. 7 Year 2017. This type of research is normative legal research by analyzing cases that conflict with the law using qualitative methods to draw deductive conclusions. The provisions for setting thresholds in presidential elections constitutionally violate the constitutional rights of citizens based on the provisions of Article 6A paragraph (2) of the 1945 Constitution which states "pairs of presidential and vice-presidential candidates are proposed by political parties or a coalition of political parties participating in general elections prior to the holding of general elections. This provision provides space for political parties to nominate presidential and vice presidential candidates. However, in Article 222 UU No.7 Year 2017 concerning General Elections, it provides a limit of 20% of the number of seats in the DPR or 25% of valid votes nationally in the previous DPR member elections. In a presidential system, the imposition of a threshold is irrelevant because theoretically the separation of powers does not recognize the president's accountability to the parliament, thus the threshold is not appropriate if the votes used are from the DPR election. Setting the threshold for presidential and vice-presidential candidates is simply reduced to 5% of seats in the DPR and 10% of valid votes from the previous general election or the article on setting the threshold for presidential and vice-presidential candidates is simply abolished through revisions to the general election law.